2017
DOI: 10.1183/13993003.02049-2016
|View full text |Cite
|
Sign up to set email alerts
|

Video-observed treatment for tuberculosis patients in Belarus: findings from the first programmatic experience

Abstract: The treatment of tuberculosis requires daily intake of multiple medications for between 6 months and 2 years, or more [1, 2]. This long duration predisposes to the interruption of medications with the risk of the emergence of drug resistance, death, disease persistence and continued transmission of tuberculosis in the community. Directly observed treatment, together with patient support, has been recommended to improve adherence [3]. However, daily treatment observation presents challenges for both patients an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 8 publications
0
31
0
3
Order By: Relevance
“…Previous studies in high-income [26,27,[30][31][32] and low-income countries [9,33] have reported high adherence and patient satisfaction with VDOT. One study from Kenya showed the promise of digital health interventions for supporting TB treatment success [34]; however, no published studies exist on the use of VDOT in Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in high-income [26,27,[30][31][32] and low-income countries [9,33] have reported high adherence and patient satisfaction with VDOT. One study from Kenya showed the promise of digital health interventions for supporting TB treatment success [34]; however, no published studies exist on the use of VDOT in Africa.…”
Section: Introductionmentioning
confidence: 99%
“…This technology may allow enhanced case management and DOT to offer a more patient-centred approach, bridging the gap between TB patients and their healthcare providers, and reducing the need for resource-intensive face-to-face encounters. Early studies have demonstrated that VOT is both feasible and acceptable to patients receiving TB treatment in the USA and Mexico 78 , and in Belarus 79 . A randomised-controlled trial comparing adherence to TB therapy when treatment is delivered by VOT vs. standard DOT among hard-to-reach patients in London has recently been completed with extremely promising initial results, though full published results are awaited 80 .…”
Section: Future Directions and Research Priorities For Treatment Adhementioning
confidence: 99%
“…61 Surveys conducted in Argentina and China suggested feasibility of SMS-based strategies due to high cellphone ownership and literacy. 52,54 Implementation studies from high-and middle-income countries (USA, Canada, Belarus, Mexico) have suggested that VDOT has high feasibility, 56,[62][63][64] though some patients had to be shifted back to in-person DOT 56 and low video or audio quality sometimes made dose observation difficult. 63,65 Ingestible sensors had high feasibility in studies conducted in the USA and Mexico, with >95% of sensor signals detected after ingestion.…”
Section: Acceptability and Ethical Questionsmentioning
confidence: 99%